1996
DOI: 10.1007/bf02350661
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of information technology in educational management for proactive development

Abstract: Evaluation will be the key to effective and efficient implementation and use of information technology in education management. As hardware, software and the needs of users develop and change, such evaluation will need to be both proactive and dynamic in that it must continually provide information concerning how the systems need to be modified to allow the potential to be realized fully. Dynamic evaluation can then be used to inform the system design, training, support and documentation to ensure end-user acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…It is applied in the assessment of the education information system to make sure the design of the system. The results of the empirical studies showed that the barriers hindering the development of the system were the restrictive orders and the complicated financial printouts [9]. Grounded on the model of UAA, this study attempts to assess the main influential factors of the acceptance of the education information system.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…It is applied in the assessment of the education information system to make sure the design of the system. The results of the empirical studies showed that the barriers hindering the development of the system were the restrictive orders and the complicated financial printouts [9]. Grounded on the model of UAA, this study attempts to assess the main influential factors of the acceptance of the education information system.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…From the outset of studies of School Information Systems, it has been a criticism that commercial systems that have been developed for use in schools have fundamental problems in limited functionality and inflexibility (Wild and Fung, 1996). In the early study the SIMS system did not map well onto the user tasks being performed manually and the users did not perceive the system as being useful.…”
Section: User Requirements and System Functionalitymentioning
confidence: 99%
“…Studies on the use of Computerised Information Systems in schools have proved the correlation between the existing variance in the type and extent of School Information System usage and the ability to adapt software to institution-specific needs (Mahnic, 1997;Wild & Fung, 1996). Flexibility is an example of a software characteristic that makes transition to new software smoother and easier.…”
Section: Introductionmentioning
confidence: 99%